Implikasi Cybercrime Pada Bisnis Digital di Indonesia - Aria Devananta (Pusat Penelitian dan Pengembangan Polri, 2021)
Technological advances have a negative and positive influence on today's technology. Starting from the news that we might be able to see on social media, there is useful information for us to be able to maximize all the activities that are currently available. All activities can run quickly and practically so it is very helpful because of the help of technology. The positive impact of current technological developments can make it easier to find information and make work easier depending on how technology can benefit a business. The negative impact of technological developments is the emergence of cybercrime in cyberspace. The purpose of this study is to describe descriptively about the cybercrime phenomenon that occurs in digital businesses in Indonesia. The research method used in this research is descriptive quantitative which tries to collect measurable information for analysis. The results of this study explain that new threats continue to increase in the growing digital business in Indonesia. Law enforcement against cybercrime which is still very minimal makes cybercrime still free in Indonesia, this is because the existing laws and regulations in Indonesia must continue to be updated like other developed countries as a preventive measure from cybercrime attacks that can threaten today's digital business.